DeterminantsAirport Revenue and Total Passengers : Airport Access, Airport Service, Pandemic Covid 19, Airlines Characteristic, and Ticket Price - Azmieti Kurnia Sinta (East Asian Journal of Multidisciplinary Research, 2023)
The goal is  to test between variables X1-X5 with Y, and  variables Y-Z, then  the result is obtained only the variable  ticket Price with the  Total Passengers is insignificant,  then the variable  airport access with variable  number of passengers  is  also insignificant, and  variable  Number of passengers with   variable Airport Income is also    insignificant.  This research is  based  on tangible results in the field and at airports  cannot  be mentioned for any reason.